2022
DOI: 10.1002/dev.22346
|View full text |Cite
|
Sign up to set email alerts
|

Face processing in the infant brain after pandemic lockdown

Abstract: The role of visual experience in the development of face processing has long been debated. We present a new angle on this question through a serendipitous study that cannot easily be repeated. Infants viewed short blocks of faces during fMRI in a repetition suppression task. The same identity was presented multiple times in half of the blocks (repeat condition) and different identities were presented once each in the other half (novel condition). In adults, the fusiform face area (FFA) tends to show greater ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…However, other fMRI and EEG data challenge that view. Two recent fMRI studies in awake infants observed face-selective responses in FFA, using different stimuli and task procedures (70, 90). For the current paper, we re-analyzed the data reported in one of these papers (70), combining data collected with different coils to more sensitively look for age-related change in face-selective responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other fMRI and EEG data challenge that view. Two recent fMRI studies in awake infants observed face-selective responses in FFA, using different stimuli and task procedures (70, 90). For the current paper, we re-analyzed the data reported in one of these papers (70), combining data collected with different coils to more sensitively look for age-related change in face-selective responses.…”
Section: Discussionmentioning
confidence: 99%
“…One important question for future research will be whether the size or selectivity of FFA in infants correspond to their face recognition abilities. Another interesting question is how the representation of face features, and face identities, in FFA changes during infancy and early childhood (90).…”
Section: Ffa In Infancy and Through Developmentmentioning
confidence: 99%
“…It could be that the reduced contacts with various talking faces, especially during the first months of life, slowed down perceptual narrowing processes. Previous studies have already shown specific face processing modes in infants growing up during the Covid‐19 pandemic (e.g., Kim et al., 2022; Yates et al., 2023). Furthermore, we did not study the effect of bilingualism on infants' social learning behavior.…”
Section: Discussionmentioning
confidence: 91%
“…A related possibility concerns the timing of this research, which took place during the COVID-19 pandemic. It is possible that the social isolation experienced as part of the pandemic changed how infants attend to familiar and novel stimuli (e.g., Yates et al, 2023), although future research will be needed to further bear upon this possibility.…”
Section: Discussionmentioning
confidence: 99%